The Effect of Sport on Preschool Children’s Physical and Mental Development: A Systematic Review (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This review sought to investigate the effect of sports on preschool-aged children’s physical and mental growth and development. Preschool age (3-5 years) is a critical development period for young children. There is accumulating evidence that children in their infancy are growing up greatly, mentally and physically. Early childhood is devoted to academic learning as much as physical activity and play. Thus, continuous healthy development should be cultivated at a young age. As part of the long-term development, sports have been found to have a positive impact on children both physically and mentally. The search range is limited to target preschool children and affective sports based on both gross/fine motor skills and cognitive/and social-emotional development. Gross motor development focuses mainly on all physical movements that involve larger muscles, while fine motor development focuses on smaller muscle groups. These developments allow children to do work that involves body side through balance, coordination, control, and movement. In fact, regular exercise affects brain development in these ways. Behaviors include memory, attention, concentration, and being able to follow instructions that directly or indirectly lead to production. The search was also limited in these developmental areas. Gross and fine motor skills encompass physical movements like bending and throwing, which are crucial for brain development. Regulating body sides aids in developing both gross motor and cognitive skills, such as attention and planning. Deficits in gross motor skills may lead to negative developmental outcomes. Evidence shows that play, gestures, shapes, and devices predict readiness in literacy, spelling, and math. Children must cultivate both primary and fine motor skills to improve physically and cognitively. Proficiency in skills related to writing formation is essential. Additionally, vocabulary plays a significant role in cognitive development, involving flexible thinking, memory control, and language management. Research highlights the importance of language in individual development.